PERAN GURU DALAM MENGELOLA KELAS - Ali Mashari; Ahmad Tohir; Husna Farhana (AHSANTA JURNAL PENDIDIKAN, 2019)
This study aims to determine the role of teachers in classroom management at SDN 23 Negerikaton. The results of this study are expected to be able to contribute to the world of education, especially to teachers to be able to carry out classroom management properly and effectively. This research is qualitative research. The method used in this research is descriptive qualitative. This research was conducted at SDN 23 Negerikaton Odd Semester Academic Year 2019/2020. Data collection techniques with interviews, observation, and documentation. The validity of the data uses technical triangulation and source triangulation. Data analysis techniques are carried out according to Miles and Huberman, through the stages of data collection, data reduction, data presentation, and drawing conclusions or verification. Based on the results of research and discussion, the conclusion of this study is in class management at SDN 23 Negerikaton through 2 management / arrangements, namely student arrangements and classroom settings. Student arrangements, the teacher initially prepares a Learning Implementation Plan (RPP) before explaining the subject matter, establishes good relations between the teacher and students, and implements student discipline. Classroom arrangement that is arranging the place and sitting position of students and accustoming students to maintain cleanliness and beauty from the beginning of entering until going home.